Theoretical studies of stripe states in underdoped cuprate superconductors - Mizutani, Soshi (My University, 2016)
In this thesis, we study stripe states in underdoped cuprate superconductors using the Bogoliubov-de Gennes (BdG) method with appropriate models. In non-self-consistent calculations, the nature of stripe states with coexisting unidirectional Pair Density Wave (PDW), Charge Density Wave (CDW), and Spin Density Wave(SDW) order is studied, and it was found that among these coexisting stripe orders, the SDW order plays a key role in reconstructing the Fermi Surface (FS), and the magnitude of SDW order needs to be relatively small in order for Fermi arcs to be realized, while strong SDW order necessarily leads to completely gapped spectra. In self-consistent calculations, we mapped out parameter regions where stripe SC states can be stabilized, which are in qualitative agreement with the generic phase diagram of cuprate superconductors. In addition, self-consistent PDW solutions with small SDW order are stabilized in some parameter region, forming small FS pockets in antinodal regions. This parameter region is a promising one to explore in future work, where self-consistent BdG calculation is to be carried out with a magnetic field in order to study the effect of magnetic field on the stability of stripes along with the possible quantum oscillations.
Keywords: cuprate superconductors; stripe